Molecular typing and drug resistance analysis of carbapenem-resistant Klebsiella pneumoniae from paediatric patients in China - Xian Zhang; Jian Xue; Mei-Jing Shen; Wen-Hong An; Ze-Qiong Chen; Kai-Feng Wu (Journal of Infection in Developing Countries)
Introduction: There are few studies on paediatric carbapenem-resistant Klebsiella pneumoniae (CRKP) in China. The present study investigated the molecular epidemiological and drug resistance characteristics of CRKP from paediatric patients in China to provide a reference for the prevention and control of CRKP infection.